Transformational Leadership in Islamic Education: A Review of Techniques and Effectiveness - Setiyono, Tri; Priyono, Pangat Ketug; Hartarto, Anggi Budi; Siswadi (International Publisher (YAPENBI), 2026)
Transformational leadership is regarded as a leadership style capable of responding to the challenges of contemporary dynamics while fostering innovation, motivation, and commitment within Islamic educational institutions. This article aims to: (1) describe the concept of transformational leadership in Islamic education, (2) identify transformational leadership techniques applied in Islamic educational institutions, and (3) analyze the effectiveness of its implementation based on literature published from 2020 to 2025. The research method employed a systematic literature review, examining scientific articles and empirical studies from journals on Islamic education and educational management. The findings indicate that techniques such as developing a collective vision and mission, staff/teacher empowerment, motivation, intellectual stimulation, and individualized consideration remain relevant and effective in improving teacher performance, innovation, work motivation, school culture, and educational quality. Recent studies also highlight the importance of work climate and organizational support as mediating factors for successful implementation. Therefore, transformational leadership remains relevant and is highly recommended for implementation in Islamic educational institutions.